1995
DOI: 10.1002/app.1995.070571202
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene‐2,6‐naphthalenedicarboxylate) fiber for industrial applications

Abstract: SYNOPSISPoly(ethylene-2,6-naphthalenedicarboxylate)(PEN) has been prepared from commercial dimethyl-2,6-naphthalenedicarboxylate (DM-2,6-NDC) and ethylene glycol (EG) according to the well-known transesterification/polycondensation route. P E N fibers, intended for industrial yarn applications, were obtained by melt spinning and drawing high molecular weight PEN. The properties of these yarns were measured in detail and compared with those of P E T industrial yarns. The development of molecular orientation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 13 publications
0
34
1
Order By: Relevance
“…These features are somewhat different from those in other reports, where the as-spun fibers produced at similar speeds reveal broad or poorly resolved scattering peaks. 6,9,11 Through an examination of the relationship between the thread-line tension monitored by online measurement and the IV and crystallinity data for individual as-spun fibers, the discrepancy between our results and others has been attributed to the high spinning stress generated by the high molecular weight polymer used in our study. 12 When the 5 km/min as-spun fiber was subjected to heat setting at various temperatures, as shown in Figure 6(b), crystalline reflections of ␣ 010 and ␣ 100 at 2 ϭ 15.7 and 23.3°start to appear at relatively high temperatures, indicating that the content of the ␣-form crystal is promoted by the annealing temperature being increased.…”
Section: Constrained Annealingcontrasting
confidence: 77%
See 2 more Smart Citations
“…These features are somewhat different from those in other reports, where the as-spun fibers produced at similar speeds reveal broad or poorly resolved scattering peaks. 6,9,11 Through an examination of the relationship between the thread-line tension monitored by online measurement and the IV and crystallinity data for individual as-spun fibers, the discrepancy between our results and others has been attributed to the high spinning stress generated by the high molecular weight polymer used in our study. 12 When the 5 km/min as-spun fiber was subjected to heat setting at various temperatures, as shown in Figure 6(b), crystalline reflections of ␣ 010 and ␣ 100 at 2 ϭ 15.7 and 23.3°start to appear at relatively high temperatures, indicating that the content of the ␣-form crystal is promoted by the annealing temperature being increased.…”
Section: Constrained Annealingcontrasting
confidence: 77%
“…Figure 10 shows the total DR as a function of the take-up velocity at which various precursor fibers were prepared, as derived from the literature 7,9 and this work. It is obvious that the total DR decreases as take-up velocity increases and approaches unity over 4 km/min.…”
Section: Hot Drawingmentioning
confidence: 99%
See 1 more Smart Citation
“…And it has been reported that the ȕ-crystal was formed by high-speed spinning or by high-temperature annealing. [16,17] It is interesting that the ȕ-rich crystal was developed by laser drawing. In…”
Section: Resultsmentioning
confidence: 99%
“…4 Huijts et al prepared high-speed spun PEN since the throughput rate was kept constant for all the take-up velocities. The intrinsic viscosity fibers and investigated the properties from the view point of industrial applications, 5 analyzed measured for the resultant fibers was 0.48 dL/ g. There was a relatively large reduction of the the mechanical behavior near the glass transition temperature, 6 and estimated the intrinsic biremolecular weight during the spinning experiment. The level of molecular weight of the exfringence.…”
Section: Introductionmentioning
confidence: 99%